Role of Bar and Restaurant Management System: Case of London Lounge, Ubungo Dar-es-Salaam - Mahuwi, Deogratias Tasilo; Hayuma, Bernad Joseph; Nkwera, Victor Simon; Ntyangiri, Christopher Denis; Mushi, Martin Ludovick (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This study aims at revealing the role played by Bar and Restaurant Management System (BRMS) in Tanzania, by studying its functionalities and user perceptions and later providing recommendations that will improve the Food and Beverage (F&B) services. London Lounge was selected as a case study to represent the middle-class bar within the country that makes use of BRMSs. The literature shows that the common design of BRMS include functionalities for accounting, inventory and employee management where the system users had positive perception on the advantages of system usage except for the inexperienced users. Focus group discussion was used as the method for data collection where the study team identified that the appropriate system users are Counter Attendants, Supervisors, Managers and the Director. The findings revealed that the system had enough functionality to exhaust the principal duties for each system user based on their job positions and hence played a big role in managing their operations. The study highlighted some system weaknesses hence provided the recommendations to improve the functionalities of the system and attract more users towards system usage. Future research on design and development of BRMS integrated with other systems to manage multiple businesses under the same ownership is highly recommended in this study.